Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1097/00000542-199808000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sevoflurane and Isoflurane on Renal Function and on Possible Markers of Nephrotoxicity 

Abstract: Low-flow sevoflurane anesthesia was associated with mild and transient proteinuria. However, the observed proteinuria was not associated with any changes in blood urea nitrogen, creatinine, and creatinine clearance in these patients with no preexisting renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 33 publications
2
60
2
7
Order By: Relevance
“…So, it seems to have no nefrotoxic effects in men 19 . Some authors have recently observed that sevoflurane in low fresh gases flow may determine renal changes, characterized by increased albumin and glucose urinary excretion, as well as of some tubular enzymes 20,21 . These results, however, have been questioned by other authors 14,22,23 for believing that the best renal changes markers are still plasma urea and creatinine levels, and for the inexistence of significant evidences to credit tubular enzyme changes as major indicators of sevoflurane-induced renal injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it seems to have no nefrotoxic effects in men 19 . Some authors have recently observed that sevoflurane in low fresh gases flow may determine renal changes, characterized by increased albumin and glucose urinary excretion, as well as of some tubular enzymes 20,21 . These results, however, have been questioned by other authors 14,22,23 for believing that the best renal changes markers are still plasma urea and creatinine levels, and for the inexistence of significant evidences to credit tubular enzyme changes as major indicators of sevoflurane-induced renal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Mais recentemente, alguns autores verificaram que o sevoflurano, quando empregado em baixo fluxo de gases frescos, pode determinar alterações renais, caracterizadas por aumento da excreção urinária de albumina e glicose, e de algumas enzimas tubulares 20,21 . No entanto, esses resultados têm sido questionados por outros autores 14,22,23 por acreditarem que os melhores marcadores de alterações renais ainda continuam a ser os níveis plasmáticos de uréia e creatinina e por não existirem evidências significativas para se creditarem às alterações enzimáticas tubulares uma indicação importante de ocorrência de lesão renal com o sevoflurano.…”
unclassified
“…Higuchi et. al [14] compared the effects of high-flow (6 l/min) and low-flow (1 l/min) sevoflurane anesthesia in patients without pre-existing renal disease in a surgical procedure scheduled expected to last 4 h. They determined markedly higher serum IF -concentrations in both low-and high-flow sevoflurane anesthesia in comparison to isoflurane anesthesia. The authors also performed 24-hour measurements of N-acetylbeta-glucosaminidase (NAG), beta-2-microglobulin, protein, glucose, BUN, and serum creatinine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that sevoflurane and its metabolites may damage renal tubule cells during renal excretion, depending on the duration of anesthesia and the toxicity ratings of degradation products. As a result of these damages, changes from in the ability of reabsorbing in the proximal tubules as far as necrosis may occur (7)(8)(9). Therefore, during anesthesia, this agent is also likely to cause toxic effects on the corneal endothelium.…”
Section: Introductionmentioning
confidence: 99%